A comparison of two methods for the detection of circulating tumour cells in patients with oral cavity cancer. (20th October 2021) - Curtin, Justin; Wong, Gordon; Wang, Weilan; Thomson, Peter; Lam, Alfred K.; Choi, Siu‐Wai
Abstract: Background: Circulating tumour cells (CTCs) detected in patient blood samples are relevant as diagnostic and prognostic markers offering insights into tumour behaviour and guiding treatment of cancer at an individualised level. The aim of this study was to ascertain the feasibility of detecting CTCs in oral squamous cell carcinoma (OSCC) using two different methods so as to determine the optimal method for the study of this cancer. Methods: Comparison of the numbers of CTCs, circulating tumour micro‐emboli (CTMs) and circulating tumour endothelial cells (CTECs), was undertaken in forty clinical samples of oral squamous cell carcinoma (OSCC) determined by filtration (ISET ® ) and in situ fluorescent immunostaining (i‐FISH, Cytelligen ® ) immunostaining and in situ hybridisation. Results: i‐FISH detected CTCs in 80% of samples compared with 40% of samples analysed by microfiltration. i‐FISH detected CTCs in a further 40% of samples in which microfiltration did not detect CTCs. No CTC clusters were detected by microfiltration while i‐FISH detected CTM in 12.5% of samples. i‐FISH analysis detected CTECs in 20/40 samples. Conclusion: These results highlight significant differences in detection of CTCs, CTM and CTECs between i‐FISH and microfiltration when applied to OSCC samples, suggesting that technologies capable of detecting circulating aneuploid cells more accurately detect CTCs. i‐FISH also detected CTM and CTEC not detected using ISET ® . With proven prognostic relevance in adenocarcinomas, accurate enumeration of CTCs, CTMs and CTECs may be a clinically useful tool in the management of OSCC and may aid in the reduction of false‐negative diagnoses.